Analysis of Decortiator Knives in Pineapple Leaf Processing Machine into Fiber Using FEA Method - Rahmatullah, Moch Zaidan; Widiantoro, Heri; Riswanda, Riswanda (Fakultas Teknik UM Pontianak, 2024)
The pineapple leaf processing machine is used to process agricultural waste that is typically discarded into economically valuable products. One important aspect in the design of this machine is ensuring that it can operate safely and effectively. Therefore, finite element analysis (FEA) numerical simulations are used to predict the behavior of the machine and optimize its design. The purpose of performing finite element analysis on the decorticator blade is to analyze whether the design model experiences plastic deformation and to predict the forces occurring during machine operation, ensuring that the machine can withstand the given load without damaging its structure. The material used for the Decorticator Blade is SS 304, consisting of 12 blades. The simulation process conducted in this research is divided into three stages: Pre-processing, Simulation, and Post-processing. The simulation process is performed 10 times using the curvature-based mesh method, with mesh sizes set to 10, 9, 8, 7, 6, 5.8, 5.6, 5.4, 5.2, and 5. The maximum stress that occurs and meets the convergence target is at mesh sizes 5.6, 5.4, and 5.2, with respective values of 44.43 MPa, 44.41 MPa, and 44.39 MPa, with the largest error accuracy of 2.49%. The results of the finite element analysis show that the design of the Decorticator Blade has a stress of 44.43 MPa and a Factor of Safety (FoS) of 6.6. Through this simulation, the design of the Decorticator Blade can be used in the machine for processing pineapple leaves into fibers.